Mediterranean diet improves liver health but does not protect against azoxymethane-induced colon tumorigenesis compared to Western diet in A/J mice - Weimin Guo; Nicholas Crossland; Jimmy W. Crott (Experimental and Molecular Pathology)
Introduction: Abundant evidence indicates that the Mediterranean (MED) diet pattern is beneficial for health, especially cardiovascular health. Epidemiological evidence indicates that the MED diet also affords protection against colorectal cancer (CRC). To date, preclinical models have only evaluated specific MED diet components and therefore, although supportive, fall short of confirming the chemoprotective capacity of this complex dietary pattern. We sought to address this gap. Method: A/J mice were randomized to receive Western (WRN) or MED diets differing in their fat, protein, and carbohydrate sources. Azoxymethane (AOM) was used to initiate colon tumorigenesis and mice were maintained for 19 weeks after the final dose. Result: Unexpectedly high mortality was observed amongst male mice following the second AOM dose. At the end of the study hepatic Cyp2E1, an enzyme that metabolize AOM, was lower in males than females. Livers from MED diet mice were significantly lighter, had lower histologic Non-Alcoholic Fatty Liver Disease (NAFLD) scores, and contained less triglycerides than WRN mice. Amongst females, serum alanine transaminase (ALT) was also lower in MED than WRN mice. Amongst male mice, those fed MED diet presented with significantly more colonic tumors than those on the WRN diet. Conclusion: In this study male mice displayed elevated sensitivity to AOM-induced hepatotoxicity and mortality than females. In agreement with human and preclinical data, livers of MED-diet-fed mice were healthier than those fed WRN diets. We could not confirm the chemoprotective capacity of the MED diet. Additional studies are required to evaluate the purported anticancer effect of the MED diet.